Mothers’ Perceptions of Infant Massage: Implications for Health Education - Wiwik Yuliati; Yuly Peristiowati (Journal of Healthcare and Biomedical Science, 2025)
Infant massage is increasingly promoted as an early stimulation practice that supports infants’ physical, emotional, and developmental outcomes. However, limited research has examined mothers’ perceptions of infant massage within community health settings in Indonesia. This study aimed to explore perceived benefits, barriers, safety concerns, and expectations for educational support among mothers, using the Nurturing Care Framework and the Health Belief Model as conceptual guides. An exploratory qualitative design was employed involving 35 mothers recruited through purposive and convenience sampling at community health centers. Data were collected using written open-ended surveys and analyzed through Braun and Clarke’s thematic analysis. Methodological rigor was ensured through triangulation, peer debriefing, and reflexive documentation. Five themes emerged. Mothers described technical barriers, including fear of making mistakes and limited confidence in performing correct massage techniques. Infant massage was perceived to support feeding comfort and breastfeeding success. While mothers showed basic awareness of safety considerations, concerns about injury and appropriate timing persisted. Massage was also viewed as a calming practice that reduced fussiness and improved sleep. Additionally, mothers expressed strong expectations for practical educational support, especially through videos, illustrated leaflets, brief classes, and live demonstrations. Demographic patterns suggested that caregiving experience, feeding practices, and economic stability may shape perceptions and confidence levels. Overall, mothers viewed infant massage positively but required accessible, structured education to ensure safe and effective practice. These findings support the integration of infant massage into maternal and child health promotion programs.